A study of fine needle aspiration cytology in salivary gland lesions in a rural population - Joshi, Anil R.; Jadhav, Dnyaneshwar S.; Baste, Balaji D.; Ranka, Shweta K. (International Journal of Advances in Medicine, 2017)
Background: Fine needle aspiration cytology (FNAC) of suspected salivary gland lesions has an established role in preoperative diagnosis and management of patients. However diverse morphological patterns and overlapping features make it a challenging job, to give a precise diagnosis at times. Methods: This was a prospective study done from October 2011 to October 2013. Fine needle aspiration cytology was performed in 64 patients with clinically significant salivary gland lesions. Results: Fine needle aspiration cytology categorized 38 (59.4%) of the salivary gland lesions as neoplastic and 26 (40.6 %) as non- neoplastic lesions. Amongst the neoplastic lesions, 86.9% were benign and 13.2% were malignant cases. Conclusions: FNAC of the salivary gland is simple, cheap, safe and reliable technique in the primary diagnosis of salivary gland lesions.